Rail Corrugation Characteristics Deduced from a Wavelet Analysis of High-Speed Train Interior Noise and Vibration - Xiaohan Phrain Gu; Yajing Han; Junming Shi; Anbin Wang (Shock and Vibration)
A method to deduce the characteristics of rail corrugation was developed and presented in this paper. It has been found that noise and vibration in the train vehicle were primarily contributed by rail corrugation and wheel polygonalisation. As the characteristics of wheel sets of a particular train can be assumed to be unchanged during a trip, rail corrugation along the tracks of the trip can be identified. Wavelet analysis was employed in analysing interior noise and vibration data collected inside a high-speed train vehicle traveling on a typical high-speed line in China. Noise and vibration data corresponding to increasing, decreasing, and unchanged train speeds were grouped and examined using time-frequency domain analysis. For both acceleration and deceleration speed conditions, the characteristic frequency of interior noise and vibration changes as the train speed changes, in a discontinuous pattern, and with a fixed speed-frequency ratio, which can be deducted as the pinned-pinned frequency of rail vibration and wavelength of rail corrugation in corresponding rail track sections. This method enables accurate restoration of rail corrugation characteristics, without having to apply for railway possession for rail corrugation tests onsite, which is an inexpensive yet reliable method to provide a basis for the formulation of line maintenance and rail grinding plans.